Superior Mesenteric Venous Thrombosis after Laparoscopic Exploration for Small Bowel Obstruction - Hideki Katagiri; Shozo Kunizaki; Mayu Shimaguchi; Yasuo Yoshinaga; Yukihiro Kanda; Alan T. Lefor; Ken Mizokami (Case Reports in Surgery)
Mesenteric venous thrombosis is a rare cause of intestinal ischemia which is potentially life-threatening because it can lead to intestinal infarction. Mesenteric venous thrombosis rarely develops after abdominal surgery and is usually associated with coagulation disorders. Associated symptoms are generally subtle or nonspecific, often resulting in delayed diagnosis. A 68-year-old woman underwent laparoscopic exploration for small bowel obstruction, secondary to adhesions. During the procedure, an intestinal perforation was identified and repaired. Postoperatively, the abdominal pain persisted and repeat exploration was undertaken. At repeat exploration, a perforation was identified in the small bowel with a surrounding abscess. After the second operation, the abdominal pain improved but anorexia persisted. Contrast enhanced abdominal computed tomography was performed which revealed superior mesenteric venous thrombosis. Anticoagulation therapy with heparin was started immediately and the thrombus resolved over the next 6 days. Although rare, this complication must be considered in patients after abdominal surgery with unexplained abdominal symptoms.